2017
DOI: 10.1097/ico.0000000000001190
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Keratoplasty at a Tertiary Referral Center in Ethiopia: Indications and Outcomes

Abstract: Purpose To describe the indications, visual acuity outcomes and graft survival after penetrating keratoplasty in Addis Ababa, Ethiopia. Methods The medical records of patients who had penetrating keratoplasty (PKP) at Menelik II Hospital between September 2000 and September 2013 were retrospectively reviewed. The pre-specified outcomes were graft survival, visual acuity, and complication rates. Results A total of 321 patients underwent penetrating keratoplasty during the study period and were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Previous studies of penetrating keratoplasty for the treatment of infectious keratitis have shown graft survival rates of 78.4%-95.0% [20][21][22]. But few reports have reported graft survival for large-diameter penetrating keratoplasty, which may be related to the rare cases of severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of penetrating keratoplasty for the treatment of infectious keratitis have shown graft survival rates of 78.4%-95.0% [20][21][22]. But few reports have reported graft survival for large-diameter penetrating keratoplasty, which may be related to the rare cases of severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…To this date, Trachoma remains the most common indication for penetrating keratoplasty in Ethiopia, 11 as the prevalence of active trachoma in some parts of Sub-Saharan Africa is among the highest in the globe. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Graft rejections were higher in cases where the etiology of the corneal opacity was different. [23][24][25] It is important to recognize that a substantial number of PKP will end up with a worse prognosis. This is particularly true when the corneal opacity is large, extending to the limbus and where the vascularization is deep and profuse.…”
Section: Discussionmentioning
confidence: 99%